Ti-6Al-4V재의 UNSM처리에 의한 축인장압축피로특성변화 - 서창민(Chang-Min Suh); 조성암(Sung-Am Cho); 편영식(Young-Sik Pyoun); 서민수(Min-Soo Suh) (Han-guk haeyang gonghak hoeji (Online), 2011)
The present study makes three original contributions to nanoskinned Ti-6Al-4V materials. The nanoskins were fabricated on Ti-6Al-4V material using various surface treatments: deep rolling (DR), laser shot peening (LSP), and ultrasonic nanocrystal surface modification (UNSM). These surface treatments are newly developed techniques and are becoming more popular in industrial fields. A fatigue strength comparison at up to 106 cycles was conducted on these nanoskinned Ti-6Al-4V materials. Fatigue tests were carried out using MTS under axial loading tension-compression fatigue (R = -1, RT, 5 Hz, sinusoidal wave). The analysis of the crack initiation patterns in the nanoskinned Ti-6Al-4V materials found an interior originating crack pattern and surface originating crack type. Microscopic observation was mainly used to investigate the fatigue fractured sites. These surface modification techniques have been widely adopted, primarily because of the robust grade of their mechanical properties. These are mainly the result of the formation of a large-scale, deep, and useful compressive residual stress, the formation of nanocrystals by the severe plastic deformation (SPD) at the subsurface layer, and the increase in surface hardness.